Implementation of the Make A Match Learning Model in Improving Vocabulary Understanding in Students at State Senior High School 6 Kendari - Nurcayang, Nurcayang; Iqbal, Muh.; Zakariah, M. Askari (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Arabic language learning at the secondary school level requires effective instructional strategies to enhance students’ vocabulary (mufradat) mastery, which serves as a fundamental component of language proficiency. However, conventional teaching methods that rely heavily on memorization often lead to low student engagement and limited vocabulary comprehension. This study aimed to examine the effectiveness of the Make a Match learning model in improving students’ Arabic vocabulary mastery at the secondary school level. This research employed a quantitative experimental approach using a true experimental design with a pre-test and post-test control group. The participants consisted of 20 students from SMA Negeri 6 Kendari, who were randomly assigned to an experimental group and a control group. Data were collected through vocabulary achievement tests, classroom observations, interviews, and documentation. The experimental group was taught using the Make a Match learning model, while the control group received conventional instruction. Data analysis was conducted using quantitative statistical techniques to compare students’ vocabulary mastery before and after the treatment. The results indicated that students who were taught using the Make a Match learning model demonstrated higher levels of vocabulary mastery compared to those taught using conventional methods. Improvements were observed in students’ pronunciation accuracy, vocabulary recognition, and ability to match vocabulary with visual representations. The interactive and cooperative nature of the Make a Match model also increased students’ motivation and active participation during the learning process. In conclusion, the Make a Match learning model is effective in enhancing students’ Arabic vocabulary mastery by promoting active learning, cooperation, and the use of visual media. This model can be considered an alternative instructional strategy for Arabic language teachers to improve vocabulary learning outcomes and create a more engaging learning environment.